Klasterisasi efektivitas penyelesaian tindak pidana di Indonesia menggunakan metode K-Means clustering - Zaidan, Muchammad Alif; Ekaputri, Enggarani Wahyu; Sari, Nur Fitriyah Ayu Tunjung (Maliki Interdisciplinary Journal, 2024)
Indonesia faces a serious problem related to the high crime rate, which is reflected in the Police statistics that show an increasing trend of criminal cases every year. This has disrupted the sense of security of the community, decreased public trust in law enforcement officials, and hindered national development. One of the main causes of the high crime rate is the suboptimal effectiveness of crime resolution, indicated by the high number of unresolved cases and the low case completion rate (TPP). Factors such as a lack of human resources and infrastructure, weak law enforcement, and suboptimal inter-agency coordination contribute to this ineffectiveness. Although the government has implemented various policies and programs to improve the effectiveness of crime resolution, significant results have not been achieved. This study aims to cluster the effectiveness of crime resolution in Indonesia using the K-Means Clustering method. This method will cluster the data based on certain characteristics, providing an overview of the factors that influence the effectiveness of crime settlement in various regions. The results of this study are expected to be the basis for formulating appropriate strategies in improving the effectiveness of criminal settlement in Indonesia.